Artificial Intelligence in Education 15th International Conference, AIED 2011, Auckland, New Zealand, June 28-July 01 2011 - Biswas, Gautam; Bull, Susan; Kay, Judy.; Mitrovic, Antonija; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 15th International Conference on Artificial Intelligence in Education, AIED 2011, held in Auckland, New Zealand in June/July 2011. The 49 revised full papers presented together with three invited talks and extended abstracts of poster presentations, young researchers contributions and interactive systems reports and workshop reports were carefully reviewed and selected from a total of 193 submissions. The papers report on technical advances in and cross-fertilization of approaches and ideas from the many topical areas that make up this highly interdisciplinary field of research and development including artificial intelligence, agent technology, computer science, cognitive and learning sciences, education, educational technology, game design, psychology, philosophy, sociology, anthropology and linguistics.
Electronic reproduction.
Keywords: Computer science; Information systems; Artificial intelligence; Artificial intelligence -- Educational applications -- Congresses; Computer-assisted instruction -- Congresses; Intelligent tutoring systems -- Congresses; Electronic books